2017
DOI: 10.4102/sajip.v43i0.1413
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and psychological capital in the Italian public administration: A new resource-based intervention programme

Abstract: Orientation: Organisations need energetic and dedicated employees to enhance the quality of their services and products continuously. According to the Conservation of Resources Theory, it is possible to increase work engagement of employees by improving their personal resources.Research purpose: The main aim of this study was to examine the extent to which an improvement in psychological capital, as a personal resource, might enhance work engagement of employees in the public sector.Motivation for the study: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 50 publications
(52 reference statements)
2
72
0
5
Order By: Relevance
“…The results of the studies show that PsychCap is highly related to WE. These results are also similar to the previous studies like Costantini et al (2017). The study`s results further explain that OC is also related to psychological capital.…”
Section: Conclusion and Recommendationsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the studies show that PsychCap is highly related to WE. These results are also similar to the previous studies like Costantini et al (2017). The study`s results further explain that OC is also related to psychological capital.…”
Section: Conclusion and Recommendationsupporting
confidence: 92%
“…No doubt the importance of PsyCap in the positive organizational behavior (POB) has widely been acclaimed conceptually and empirically, it does not warrant that all organizations would accrue its benefits. Public sector organizations, famous for negative connotations like stagnancy and inefficiency (Goodsell, 2003), and suffering from structural weaknesses (Costantini et al, 2017), which have been dubbed organizations with 'human capital crisis' (Jacobson, 2011), appear to be out of the spectrum of Global Social Sciences Review (GSSR) benefits attached with it. In countries where the public sector is more dominant, health would definitely be the public-sector domain.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, organizations can perform some interventions and remedies. For example, it has been shown that resource-based intervention programs that build the psychological capital of employees help to improve employees’ work engagement and to build strong relationships between employees and the organization (Costantini et al, 2017). In addition, the organization can obtain the employees’ understanding by explaining the reason for the breach and compensating the employees in other ways (Morrison and Robinson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Our results appear to indicate that if HRM specialists wish to enhance employee work engagement, more attention should be paid to building supportive and resourceful job environments, e.g. by JD-R intervention aimed at increasing personal and job resources (Wingerden et al 2016;Costantini et al 2017) Finally, it must be remembered that financial rewards are a vital and significant part of every job and, as such, have a tremendous role to play as HRM tools, especially in fulfilling employees' basic needs, attracting and retaining the best employees, increasing performance, or showing appreciation towards teams and individuals (Shaw and Gupta 2015). However, though remuneration packages might be useful tools, they might not be a onesize-fits-all solution for the purposes of HRM, and here our study seems to suggest that financial rewards are weakly related to work engagement.…”
Section: Discussionmentioning
confidence: 99%